Descriptive norms and corruption: Examining the moderating role of ethical leadership - Manara, Muhammad Untung; Widodo, Rinto Wahyu; Hidayatullah, Moch Syarif; Mardhiah, Mardhiah (Faculty of Psychology, Universitas Diponegoro, 2024)
Background: Corruption is one of the major inhibitory to various advances. Corruption that was characterized by misuse of public or organizational positions for personal or organizational benefit commonly involved public officials in the form of bribery behavior. Therefore, it is important to investigate factors contributing to bribery behavior in public officials. Purpose: Taking a micro-level perspective, this research aims to extend corruption literature by focusing on the moderating role of ethical leadership in the relationship between descriptive norms and corruption. Method: The study used a quantitative survey approach with 116 participants working in public organizations. Three scales were used to measure descriptive norms, ethical leadership, and corruption. A moderation regression-based analysis was used to analyze the data. Findings: The results showed that descriptive norms have a significant role in predicting corruption. However, ethical leadership has no moderating role in the relationship between descriptive norms and corruption. Implication: These findings provide new insight into the literature by suggesting that ethical leadership might not be effective in reducing followers’ corruption when corruption is widespread. Therefore, corruption intervention programs may emphasize descriptive norms aspect in anti-corruption campaigns to reduce the perception of descriptive norms in order to reduce the possibility of individuals engaging in corruption.